PSVII-18 Role of azoximer bromid in functional system «mother-fetus» in cows. (30th November 2020) - Filatov, Andrey; Shemuranova, Natal'ya; Sapozhnikov, Alexander; Anipchenko, Polina; Eremin, Sergey; Nikitin, Georgy; Plemyashov, Kirill
Abstract: The aim was to study efficiency of Azoxivet (azoximer bromid) for prevention of cows' postnatal diseases and indirect influence on calves' growth. Groups of pregnant Holstein cows (> 6000 kg per lactation) were formed (G1, G2, G3). Cows of G1 (n = 20) received Azoxivet intramuscularly once at 7 days prior to expected date of calving at a dose 24 mg. G2 (n = 20) - 24 mg at 14 and 7 days prior to expected date of calving. G3 (n = 20) was control. Single application of Azoxivet at 7 days prior to calving doesn't lead to lowering trouble of postnatal endometritis: this disease was registered at 60% cows of G1 and 65% cows of G3. In G2, endometritis was recorded only at 40% of animals. The density of the colostrum in of G1 and G2 was varied: 1060.0±3.1-1063.0±2.9 kg/m3, which exceeded the indicator of the G3 by 13–16 kg/m3 (P < 0.05). There was increased amount of whey proteins in colostrum obtained from cows of G1 and G2: the differences were 6.4% and 19.2% (P < 0.05). In the G3 it was 220.5 ± 12.6 g/l. The amount of total immunoglobulins in the colostrum in G1 was 159.7 ± 9.6 g/l, in G2 - 180.6 ± 4.0 g/l, that was higher than in the G 3 by 35.0% (P < 0.05). The incidence of calves received from cows of G1 and G2 was lower than 15%, than G3, and the safety to the 2-month age was 90–95% against 85% in G3. The average alive mass of 1 calf in G3 was 77.5±1.6 kg that was lower than in G1 by 5.7% (P < 0.05), in G2 – by 9.6% (P < 0.01). The mediated immune-correction with Azoxivet through the system of fetus-mother allows to reduce incidence, to increase viability of calves in the first 2 months of life.